1999
DOI: 10.1080/02844319950159659
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Facial Growth in Patients With Unilateral Cleft Lip and Palate Treated by Different Regimens for Two-Stage Palatal Repair

Abstract: The aim of this study was to compare facial development, particularly growth of the maxilla, of two groups of patients with unilateral cleft lip and palate in whom palatal surgery had been done slightly differently, particularly the timing of the procedures. Two-stage palatal repair had been used at 8 (velar closure) and 102 months (hard palate surgery) at one cleft centre and at 20 and 62 months at another centre. Lateral roentgencephalograms were used to analyse the first sample of 20 patients, who were foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 3 publications
0
13
1
1
Order By: Relevance
“…Noverraz et al (1993) reached the same conclusion after analyzing the dental casts of four different patient groups whose hard palates had been closed at various times. Likewise, Friede et al (1999) could not state an evident difference in midfacial growth in two groups of patients who underwent delayed hard palate surgery at two different time points. Gaggl et al (2003) compared two groups of adult patients and reported the development of sagittal and transversal maxillary dimensions to be even better in the group who had undergone the single-stage procedure.…”
mentioning
confidence: 67%
“…Noverraz et al (1993) reached the same conclusion after analyzing the dental casts of four different patient groups whose hard palates had been closed at various times. Likewise, Friede et al (1999) could not state an evident difference in midfacial growth in two groups of patients who underwent delayed hard palate surgery at two different time points. Gaggl et al (2003) compared two groups of adult patients and reported the development of sagittal and transversal maxillary dimensions to be even better in the group who had undergone the single-stage procedure.…”
mentioning
confidence: 67%
“…Many authors 1,4,5,7,12 noted reduction of maxillo-mandibular discrepancy (ANB) in cleft patients. The present results indicated a significantly decreased ANB angle in group I patients (p < 001) compared with groups II and III.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6]11 Different management protocols have different impact on the development of craniofacial morphology. 4,7,8,13,15,[17][18][19]24,[27][28][29] This study has compared the craniofacial morphology of children with complete unilateral cleft lip and palate treated with three different surgical protocols, the only difference which is in the technique employed to perform hard palate closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FRIEDE et al 3 questioned whether it is necessary to delay closure until 9 years of age rather than 5 years, because similar and satisfactory maxillary growth was found in two samples in which patients underwent surgery at the two different ages. They speculated that by starting closure of the soft palate, the size of the remaining hard palate narrows spontaneously 17 , facilitating a smaller, less invasive, later hard palate repair.…”
mentioning
confidence: 96%